Kualitas Layanan dan Promosi Terhadap Loyalitas Melalui Kepuasan : Studi Pelanggan Cafe One More Palangka Raya - Rahmi aulia; Achmad Syamsudin; Lelo Sintani (Edunomics Journal, 2023)
This study aims to analyze the effect of service quality and promotion on loyalty through customer satisfaction. The research method used is a quantitative method with data collection techniques using questionnaires and observation. Data analysis uses reflective and formative constructs. The data used in the form of primary data with analysis tools using SmartPLS03. This research was conducted for one month from the month. The results of this study are service quality has a positive and significant effect on customer satisfaction, promotion has a significant positive effect on customer satisfaction, service quality has an insignificant negative effect on loyalty, promotion has a significant positive effect on customer loyalty, customer satisfaction has a significant positive effect on customer loyalty, customer satisfaction able to mediate between service quality variables and customer loyalty, satisfaction is able to mediate promotion variables and customer loyalty.